A case of congenital insensitivity to pain with anhidrosis with sensitivity reactions to the electric pulp test. Issue 2 (August 2017) - Isogawa, Nobutaka; Ito, Kaori; Lee, Justin; Ikeda, Masakazu; Ishikawa, Masaaki; Baba, Yoshiyuki
Abstract: Background/Purpose: Congenital insensitivity to pain with anhidrosis (CIPA) is a rare autosomal recessive disorder characterized by anhidrosis, lack of pain sensation, and mental retardation. Mutations in the NTRK1 gene are responsible for this disorder and cause the apoptosis of A-δ and C nerve fibers. Methods and Results: A 6-year-old boy with CIPA showed sensitivity reactions to the electric pulp test in some teeth. Conclusion: If A-β nerve fibers respond positively to the electric pulp test, it could potentially be used to diagnose the pulp vitality of CIPA individuals. However, it is possible that this is an exceptional CIPA case that retained sensitivity to some stimuli.